Hair Wash: improving hair transplantation - Farid Bark Hamdar; Sandro Navarro Salanitri; Lauro Fumiyuki Otsuka Junior; Gabriela Suemi Shimizu; Christiane Steponavicius Sobral (Revista Brasileira de Cirurgia Plástica)
An efficient use of operative time is a concern regarding not only hair transplantation but all surgical procedures. In case of large areas to be transplanted, no more than 6 hours per session is recommended, to avoid damaging transplanted hairs. We developed a device using sterilized materials, with the exception of a compressed air flowmeter, support serum, and compressed air, which remain outside the surgical field. The "Hair Wash" device shortened the operative time and improved the surgery. The "Hair Wash" device is feasible and easily replicable, and improves the hair transplant procedure.